Histomorphometric analysis of the temporal bone after change of direction of force vector of mandible: an experimental study in rabbits - Edela Puricelli; Deise Ponzoni; Jéssica Cerioli Munaretto; Adriana Corsetti; Mauro Gomes Trein Leite (University of São Paulo, 2012)
OBJECTIVES: The present study aimed at performing a histological evaluation of the response of temporal bone tissue to a change of direction of the force vector of the mandible in relation to the base of the skull. MATERIAL AND METHODS: Adult rabbits were assigned into four groups with two control and four experimental animals in each group. experimental animals underwent surgery, which resulted in a change of direction of the force vector on the right temporomandibular joint. Samples were collected after 15, 30, 60 and 90 days for histological analysis. RESULTS: In the two-way analysis of variance, the effect of group and time was statistically significant (p<0.001). Additionally, a statistically significant interaction between group and time was observed (p<0.001). Control animals showed normal growth and development of the temporal region. In the experimental group, the change in direction of the force vector of the mandible induced significant changes in the temporal bone, with a bone modeling process, which suggests growth of this cranial structure. CONCLUSIONS: The methodology used in this experiment allows us to conclude that the change in direction of the force vector of the mandible in relation to the skull base induces remodeling and modeling processes in the temporal bone. The resumption of normal oral functions after bone healing of the mandibular fracture appears to increase cell activation in the remodeling and modeling of the temporal bone structure. The observation of areas of temporal bone modeling shows the relevance of further investigation on the correlation between the joint structures and craniofacial growth and development.